An application of DINESERV at restaurants in Changi Airport Terminal 3. - Chan, Rina Hui Bin. (2009)
Changi Airport Terminal 3 intends to position itself as a shopping destination for non-travelling locals with significant space dedicated to retail and food and beverage outlets. However, retailers have been facing lacklustre business since its inception. To aid in finding out its cause, this study undertook a service assessment of the selected food outlets within the public areas of the terminal. The SERVQUAL methodology was adopted with a modified DINESERV questionnaire as the survey tool. Six restaurants were classified into Full Service, Quick Service and Café restaurant types. Random patrons were asked to respond with their adequate, desired and perceived service levels for the respective restaurants. Respondents were found to have ranked hygiene factors and prompt accurate services as their main expectations. ANOVA analysis showed that the customers had significantly different expectations for the Full Service Restaurants as compared to the Quick Service Restaurants and Café types. Through the computation of the Measure of Service Adequacy and Measure of Service Superiority gaps, Full Service Restaurants had competitive disadvantage while both Quick Service Restaurants and Cafés achieved competitive advantages. Recommendations were proposed to narrow these service gaps. Overall, this research has essential information that will help the restaurants understand its customers and its performance better. From this, the restaurants can channel efforts appropriately so as to achieve an improved fit with the target customers’ needs.